HISTÓRIA/MEMÓRIA NO MUSEU VISCONDE DE GUARAPUAVA: VISIBILIDADES E APAGAMENTOS DA ESCRAVIDÃO NEGRA - CANALLI, MARIA LUCIMAR (2020)
Our discursive object is the Viscount of Guarapuava Museum, cutting the black slavery. We affiliate the Discourse Analysis and, based on this theoretical field, we assume that language in history allows the interpretation that is never closed and homogeneous. We discuss Discourse Analysis as a discipline interlaced, in which the subject is condemned to interpret. We conceive history by the historicity that it engages as discursiveness. At the border between the domain of the discursive of history and memory, we formed a corpus and built an archive from the ruins of the slaves' quarters, taken from the museum itself, from plates, documents and discursive sequences from the discourse of history, focusing on historians and researchers from Guarapuava. The discourse of history establishes a narrative about black slavery and the relationship between discourse, subject, and history by means of the language always incomplete carry out a discursive reading, seeking to answer the following research question: How does the museum structure itself and give visibility or erase black slavery and its relationship with the Viscount of Guarapuava? The general objective of the thesis, in order to answer this question, was to verify what the history does not say, attempting to understand the 'unspoken' and to identify the silences of this discourse to know how this memorial space is structured and what is visible in it, or deleted from subjects involved in its historicity. It demands from the general objective and the theoretical perspective in which we enroll to take the museum as a discourse, which functions as a body-memory and a body-document. The thesis is divided into three chapters that cover our object and give visibility to the conditions of production of this discourse, as well as to the subjects that are part of colonization and black slavery as one of the urbanization mechanisms of the city of Guarapuava. The history discourse focuses on two subjects: Antonio de Sá Camargo - the Viscount of Guarapuava - and Belmiro Sebastião de Miranda - the slave-abolitionist. The writing of the thesis showed that both, according to historians, defended the freedom of slaves, but registered themselves in different discoursive formations, so that slavery means differently. In terms of the museum, it is reasonable to mark as a possible conclusion, that although this space means as a place of memory, the subjects occupy different places and, discursively, it is due to the acquis and silences, unspoken and the underground memories resonate, constituting mistakes and displacements. In addition, history discourse often leads to the idealization of subjects, but the ruins of the slaves' quarters, the museum's acquis and reading beyond literality signal displacements, ruptures, and contradictions. The discoursive research presupposes the commuter movement (PETRI, 2013) and demands from this movement backwards and forwards from the corpus to the theory and the mobilization of theoretical concepts, in this thesis, the subject and the ideology and the conditions of production help to produce the discoursive web, through which the past, the present, and the future echo, highlighting in this way the memories of black slaves and slave traders that still resonate and make sense in the museum and in the city of Guarapuava.